2013
DOI: 10.1111/ggi.12037
|View full text |Cite
|
Sign up to set email alerts
|

Association of sarcopenia with functional decline in community‐dwelling elderly subjects in Japan

Abstract: Sarcopenia, defined by muscle mass, muscle strength and physical performance, was associated with functional decline over a 2-year period in elderly Japanese. Interventions to prevent sarcopenia are very important to prevent functional decline among elderly individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 20 publications
(69 reference statements)
4
87
1
3
Order By: Relevance
“…Patients with sarcopenia show a worse swallowing ability and a lower nutritional status than those without it. Furthermore, older men (>65 years of age) with sarcopenia showed lower ADL values than patients without sarcopenia (7,8).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Patients with sarcopenia show a worse swallowing ability and a lower nutritional status than those without it. Furthermore, older men (>65 years of age) with sarcopenia showed lower ADL values than patients without sarcopenia (7,8).…”
Section: Discussionmentioning
confidence: 90%
“…Other recent studies have revealed that sarcopenia is a risk factor for postoperative complications or a poor survival in some solid cancers. For stage 2-3 gastric cancer, patients with sarcopenia showed a higher rate of postoperative complications and a poorer overall and recurrence-free survival than those without sarcopenia (8,11). Pancreatic cancer patients with sarcopenia who underwent pancreatectomy also showed a poorer overall survival than the patients without sarcopenia (12).…”
Section: Discussionmentioning
confidence: 98%
“…Ideally, specific cutoff points for sarcopenia should be determined for each specific patient population and race. There have been a few reports that defined a cutoff point for sarcopenia in Japanese [31,32]. Based on these studies, we defined the cutoff point as the gender-specific 20th percentile in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle mass decreases by about 25% from the age of 50 to about 75 compared to the amount of muscle at the age of 20 and physical abilities such as balance and flexibility noticeably decrease [28,29]. Due to this deterioration of physical functions, the risk of falling increases and falls increase the risk of fracture [30,31], causing a vicious cycle in which hypoactivity causes amyotrophia [32]. It has been reported in many studies that there is a positive correlation between BMD and exercise.…”
Section: Discussionmentioning
confidence: 99%